POLYHERBAL SHAMPOO POWDER - Prashant, Akula Nikhil (Asian Journal of Pharmaceutical and Clinical Research, 2015)
OBJECTIVE: To formulate a Poly herbal shampoo powder containing natural ingredients with an emphasis on safety and efficacy which will avoid the risk posed by chemical ingredients. It clears sebum, dirt, dandruff, promotes hair growth, strengthens and darkens hair. Moreover it also acts as a conditioning agent and performs all these actions without affecting or damaging hair. The herbs Amla, Bhringaraj, Hibiscus, Shikakai and Ginger have been selected to formulate the poly herbal shampoo powder on the basis of a traditional system and scientific justification with modern uses. METHOD: Poly herbal shampoo powders were accurately weighed, passed through sieve no.100, prepared by mixing in their ascending order of quantities with continuous trituration, stored in air tight containers and used for further studies. All the five formulations (F1-F5) were subjected to organoleptic studies, general powder charecterstics, physicochemical evaluation, ash and alcohol soluble extractives, moisture content determination, pH determination, cleaning action, foaming capacities, dirt dispersion, wetting time and studies on nature of hair after wash. RESULTS: All the five formulations (F1-F5) offered a suitable practical approach and achieved a better usage. General powder characteristics showed results in specified limits. Physicochemical evaluations, pH determination, ability to remove grease, foaming capacity, dirt dispersion, wetting time and nature of hair after wash were found to yield satisfactory results for F2 formulation. CONCLUSION: The present work confirmed the successful preparation of Poly herbal shampoo powders by mixing method without using other excipients in different concentrations. Amongst all the five formulations (F1-F5) F2 yielded satisfactory results. KEY WORDS: Poly Herbal shampoo powder, Formulation & Evaluation methods